PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV USAHA BERSAMA” - Nadia Septiani; Sungkono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
“This research aims to determine the influence of motivation and work discipline on employee performance at CV Usaha Bersama. Motivation (internal and external) and discipline (obedience and responsibility) are factors that are considered important influencing performance. The research was conducted on all 32 employees using a saturated sampling technique. The regression results show the equation: (Y = 3.837 + 1.450X1 + 0.062X2 + e), which indicates that work motivation (X1) and work discipline (X2) have a positive influence on performance. Partially, work motivation has a significant effect, while work discipline has no significant effect on performance. However, simultaneously both have a significant influence on performance. The coefficient of determination of 0.482 or 48.2% shows that the contribution of motivation and work discipline to employee performance reaches 48.2%, while happiness is influenced by other factors”.